Evaluasi Kinerja Saluran Primer Pada Jaringan Irigasi Bendung Argoguruh Wilayah Adipuro Tegineneng Lampung Tengah - Yuni Laras Setyawati; Iskandar Zulkarnain; I Gde Darmaputra (Jurusan Teknologi Pertanian, 2014)
The primary channel of Argoguruh located in Central Lampung regency. Argoguruh weir has two primary channels which is named by Kanal One and Kanal Two. The decreasing performance and damage occurs with increasing age of the building. The purpose of study is to determine the performance of the primary channel Kanal One on Argoguruh weir irrigation network. Total length of the Cannal One on this study is about 9 km, which is measured from intake to distribution box on channel segmen KH2. The method of research is conducted by direct observation in the field with determine the velocity, the dimensions of the existing primary channel and sedimentation volume. The secondary data like as the channel dimensions, discharge plans, schemes of irrigation networks, rainfall data, and climatology were collected to support for hydrologic analyst. The rainfall data and climatological data are used to calculate the water needed for irrigation , than the value of the water needed is used to calculate water discharge plan that will be used as a comparison to the existing discharge channel. The results of this study showed the water discharge in existing channel of 32.17 m3/s was able to drain the water in accordance with the discharge plan for 31.64m3/sec. The volume of sediment in the primary channel as 49344.55m3, the potential for sediment deposition during the year amounted to 471.62mm /yr, loss of water in the channel is about 0.12% and the efficiencies of primary channels is about 99.88%.Keywords: performance evaluation, primary channel, Argoguruh,